VIDEO INTEGRATION IN COLLOCATION INSTRUCTION: A PEDAGOGICAL APPROACH FOR EFL CLASSROOMS - KENJAEVA, Diana Shermatovna (The Lingua Spectrum, 2025)
The attainment of collocational competency is essential for achieving native-like fluency for EFL learners since it demonstrates the capacity to utilize words in natural and contextually suitable combinations. This article examines a methodological framework for instructing English collocations to EFL learners via incorporating video content. The study focuses on the use of internet video materials to facilitate learning English collocations in EFL classrooms as well as attempting to generate various approaches to define collocations. The findings indicate that video-supported instruction enhances both receptive and productive collocational competency. The paper contends that video integration not only serves as an authentic and contextual language input but also facilitates lexical and collocational competence. However, the integration of video content into teaching collocational instruction needs further research.